ERRORS ANALYSIS OF LANGUAGE FUNCTIONS USED BY THE LOCAL GUIDES IN DANAU TAMBLINGAN BULELENG BALI - Thiana, P.G.E.; Budasi, I.G.; Pratiwi, N.P.A. (Universitas Pendidikan Ganesha, 2018)
This study was aimed at identifying the language functions, analyzing the types of errors in and identifying the sources of errors committed by local guides in DanauTamblingan. This study was a descriptive qualitative research. The subjects of this study were three local guides in DanauTamblingan. The data were collected through observation and interview. Interactive data analysis model was used to analyze the data. The results of this study show that 14 language functions namely advising, thanking, greeting, refusing, self-introduction, offering something, asking information, giving information, explaining something, giving suggestion, giving command, telling prohibition, apologizing, and saying goodbye. There were 4 types of error: omission, addition, misformation and misordering. The total number of errors were 579 which consisted of 365 errors or 63.0% in omission, 103 errors or 19.0% in addition, 93 errors or 15% in misformation and 18 errors or 3.0% in misordering.